2007
DOI: 10.1631/jzus.2007.b0170
|View full text |Cite
|
Sign up to set email alerts
|

What we know about ST13, a co-factor of heat shock protein, or a tumor suppressor?

Abstract: This article is to summarize the molecular and functional analysis of the gene "suppression of tumorigenicity 13" (ST13). ST13 is in fact the gene encoding Hsp70 interacting protein (Hip), a co-factor (co-chaperone) of the 70-kDa heat shock proteins (Hsc/Hsp70). By collaborating with other positive co-factors such as Hsp40 and the Hsp70-Hsp90 organizing protein (Hop), or competing with negative co-factors such as Bcl2-associated athanogen 1 (Bag1), Hip facilitates may facilitate the chaperone function of Hsc/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…This region harbours several genes, for instance, ST13 (suppression of tumourigenicity 13), which encodes a cofactor of the heat shock protein 70. ST13 has been found to be down-regulated in gastric and colorectal cancers (Shi et al 2007), and a potent antitumour effect of ST13 has recently been reported in vitro and in an animal model of colorectal carcinoma (Yang et al 2008). A second MOR of deletion at 22q13.2-22q13.31 involved 50% of the tumour samples.…”
Section: Discussionmentioning
confidence: 99%
“…This region harbours several genes, for instance, ST13 (suppression of tumourigenicity 13), which encodes a cofactor of the heat shock protein 70. ST13 has been found to be down-regulated in gastric and colorectal cancers (Shi et al 2007), and a potent antitumour effect of ST13 has recently been reported in vitro and in an animal model of colorectal carcinoma (Yang et al 2008). A second MOR of deletion at 22q13.2-22q13.31 involved 50% of the tumour samples.…”
Section: Discussionmentioning
confidence: 99%
“…(19)(20)(21) By collaborating with other positive cofactors such as Hsp40 and the Hsp70-Hsp90 organizing protein, or competing with negative cofactors such as Bcl2-associated athanogen 1, Hsp70-interacting protein may facilitate the chaperone function of Hsc70 and Hsp70 in protein folding and repair, and in controlling the activity of regulatory proteins such as steroid receptors and regulators of proliferation or apoptosis. (21)(22)(23) Our recent findings suggest that overexpression of ST13 can inhibit the growth of wild-type and mutant p53 colorectal cancer cells by inducing mitochondrial apoptotic cell death.(24) This evidence clearly proves that ST13 is a colorectal cancer-specific suppressor gene.To create an oncolytic adenovirus with stronger antitumor targeting efficacy and reduced side effects on normal cells, the novel adenovirus variant SG500 was constructed, in which the tumor-selective expression of both the E1A and E1B genes was replaced with the hTERT promoter and HRE promoter, respectively.(12) The ST13 expression cassette controlled by the cytomegalovirus promoter was inserted into SG500 to form SG500-ST13 constructs, allowing for increased cancer cell targeting specificity and decreased adverse side effects. Its antitumor efficacy was explored both in vitro and in vivo.…”
mentioning
confidence: 99%
“…ST13 is the gene encoding the HSP70 interacting protein (HIP), a co-chaperone of the 70-kDa HSPs (HSC/HSP70) (Höhfeld et al, 1995;Shi et al, 2007). We originally identified the ST13 gene by subtraction hybridization with normal mucosal tissue and colorectal cancers (Zheng et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…ST13 protein (HIP) is composed of an N-terminal region, a central tetratricopeptide repeat (TPR) domain followed by a highly charged region, and a C-terminal region containing glycine-glycine-methionine-proline (GGMP) repeats and a Sti1 motif (Prapapanich et al, 1996a;1998;Irmer and Höhfeld, 1997). HIP may facilitate the chaperone function of HSC/HSP70 in controlling the activities of regulatory proteins such as steroid receptors and regulators of proliferation or apoptosis, and in protein folding and repair (Prapapanich et al, 1996a;1996b;Höhfeld and Jentsch, 1997;Irmer and Höhfeld, 1997;Shi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%